Comparison of Pre- and Posttreatment Airway Volume in Patients with Temporomandibular Joint Disorders Treated with Ultra-Low Frequency Transcutaneous Electrical Nerve Stimulation Using Cone Beam Computed Tomography - Rhea Susan Verghese; Renju Jose; Anu Ramachandran; Aravind M. Shanmugham; Priya K. Nair; Krishna S. Kumar; Beena R. Varma (International Archives of Otorhinolaryngology, 2023)
Introduction Temporomandibular joint disorders (TMD) present with a multitude of symptoms that can range from headaches to shoulder pain. Patients frequently present with pain in the ear, dizziness, and vertigo. It is noted that some patients who report TMDs also have a history of sleep disturbances, which is noted in cone beam computed tomography (CBCT) as a reduction in the oropharyngeal airway volume.